Analysis of Settlement Patterns and Flood Resilience in the Bingai River Border Area, Binjai City - Usman; Ruri Prihatini Lubis; Abdiyanto (Equivalent : Journal of Economic, Accounting and Management, 2026)
Riverbanks constitute an essential component of urban spatial systems, functioning as ecological buffers as well as spaces for community activities. In rapidly developing urban areas, riverbanks are often subjected to intense land-use pressure, which may lead to environmental degradation and increased hydrological vulnerability. This study aims to formulate strategies for the arrangement and restoration of the Bingai River riverbank based on existing conditions and the watershed (DAS) management policy framework. The research employs a descriptive approach combining qualitative and quantitative methods, complemented by SWOT analysis as a strategic synthesis tool. Data were collected through field observations, documentation, questionnaires administered to communities living along the riverbank, and a review of secondary data and relevant policy documents. The results indicate that the existing conditions of the Bingai River riverbank are not yet fully aligned with watershed management and spatial planning policies, as reflected by settlement pressure, limited riparian vegetation, and suboptimal environmental infrastructure. The SWOT analysis generates strategic directions emphasizing the strengthening of riverbank ecological buffer functions, gradual control of riverbank land use, and the integration of riverbank arrangement with existing watershed management policies and programs. This study is expected to provide an initial reference for the contextual and applicable management of urban riverbanks.